Filtration calculation to reduce the construction impact on hydrogeological conditions in the city - Glazunova Irina; Sokolova Svetlana; Shiryaeva Margarita (Magazine of Civil Engineering)
The paper presents the results of the research conducted to justify construction works within the intensively developed and still developing city area. The study area was located structurally and tectonically within the lowered part of the grabens bounded by regional gaps. The second from the surface aquifer was confined. The aim of the research was to evaluate the effect of lowering of the water table during construction work and laying utility lines on the filtration properties of soils, as well as on existing buildings and highways. Analytical dependencies for the infinite linear perturbation source scheme in an infinite soil layer were proposed and improved. The conducted modeling showed that the estimated maximum depression at the design point under the multi-storey non-residential administrative building was 4.4 m, which was less than the maximum allowable deformations. It was revealed that the maximum water inflows were observed at lowering of water table over the entire limited area of 20–40 m length simultaneously; therefore, the obtained analytical solution should be increased by 22.4 %. It was found that the average discharges depend proportionally on the amount of subsidence in the water table lowering area, with the relationship between the average discharges being linear regardless of the design scheme. The building subsidence due to water table lowering was calculated and a model for geofiltration calculations was developed in Microsoft Excel. The model calculations showed that the maximum subsidence of the soil at the design point of the multi-storey non-residential administrative building did not exceed the maximum allowable deformation values.